Lasciar spazio ai margini dell’abitare: friche, progettualità ed enjambement (Itinera, 2024)
This article discusses the concept of the “Third Landscape” proposed by Gilles Clément, examining its relationship to architectural design and the conception of time and the subject. By analyzing the philosophical implications of the notion of friche, it aims to reconsider our anthropocentric worldview in order to embrace an approach that recognizes and values the richness of life in the residual. The text explores the complexity of relationships between humans, nature and architectural space, questioning traditional concepts such as the Promethean idea of the subject and time as a linear progression. Thus, a new model of designing subjectivity based on the Merleaupontyan institution is suggested, one that recognizes contingency and anonymity as essential elements of creation, thus emphasizing the need to reconsider as an authentic ethical and political value the letting-space.
Keywords: friche, architecture, design, nature